REPRESENTASI PRIBUMI DALAM NJAI DASIMA VERSI TH. MANUSAMA - Sungkowati, Yulitin (ATAVISME, 2007)
Nyai Dasima story accurately reflects some problems deal with the politics of identity and the complexity of relation between colonized. The politics of identity strategy which is implemented by colonizers could be traced in literary works. Th. Manusama Njai Dasima that is written in colonial era reflects its strategy in the representation of pribumi or 'native' as a villainous and greedy character. Claiming for Islamic value, the native is portrayed as a bandit who greedily holds up the white's wealth. The natives are also depicted easily killing each other merely due to material goods. In order to influence the readers, colonizers strive to destroy the native reputation and Islamic value. As a part of colonialist, Th. Manusama, as a part of the colonizer, has an intention to enhance the hegemonic colonial power by represents that the natives voluntarily accept colonial power by represents that the natives voluntarily accept colonialism.